2012
DOI: 10.1530/eje-12-0007
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of ghrelin and the GH/IGF axis to high altitude

Abstract: Objective: High altitude (HA) provokes a variety of endocrine adaptive processes. We investigated the impact of HA on ghrelin levels and the GH/IGF axis. Design: Observational study as part of a medical multidisciplinary project in a mountainous environment. Methods: Thirty-three probands (12 females) were investigated at three timepoints during ascent to HA (A: d K42, 120 m; B: d C4, 3440 m; C: d C14, 5050 m). The following parameters were obtained: ghrelin; GH; GH-binding protein (GHBP); IGF1; IGF2; IGF-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
2
Order By: Relevance
“…Several studies have already investigated various hormone concentrations at high altitude ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already investigated various hormone concentrations at high altitude ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported plasma levels of CCL18 are higher in HA subjects than in LA participant, 53 which is similar to our results. Moreover, Riedl et al 54 demonstrated that IGFBP2 levels increased during ascent to high altitude. However, in our validation set, IGFBP2 showed no obvious difference in the two cohorts.…”
Section: Hypoxia-inducible Factor 1α Induced Alterations Of Protein E...mentioning
confidence: 99%
“…Untersuchungen nach zusätzlichen Stressoren wie sportlichen Aktivitäten auf simulierten 4000 und 5500 Höhenmetern [24], einem Aufstieg auf 5050 m [25] oder der Besteigung des Mount Everest [3] führten zu einem Anstieg der Somatotropinkonzentration.…”
Section: Somatotropinkonzentrationunclassified